DOP49 Metagenomic Characterisation of The Colonic Mucosa-Associated Microbiota Reveals Novel Microbes and Communities in Health and Crohn's disease. The ENIGMA study. (30th January 2023) - Kang, S; Teh, J J; Zhang, J; Hu, J; Hamilton, A L; Wilson-O'Brien, A; Trakman, G L; Lin, W; Ching, J; Sung, J J Y; Yu, J; Ng, S C; et al.
Abstract: Background: Deep functional understanding of the mucosa-associated microbiota (MAM) in Crohn's disease and health by DNA sequencing approaches is restricted by the dominance of human DNA in samples. We established an ex vivo combination of tissue preservation, microbe culture, and metagenomic sequencing to overcome this knowledge gap 1 and applied this approach to characterise the colonic MAM from two populations with different Crohn's disease epidemiology (Hong Kong and Australia) and in comparison to healthy subjects. Methods: Biopsies (right colon) were cryopreserved from 100 participants in the Eastern IBD Gut Microbiota (ENIGMA) study, with 59 Crohn's disease (29 from Australia) and 41 healthy subjects (20 from Australia). The MAM were recovered from these samples 1 and taxonomic and functional assessments of their metagenomes was performed using the HUMANn3 pipeline. Metagenome-assembled genomes (MAG) were produced using the MetaWRAP pipeline, and their taxonomy determined via the Genome Taxonomy Database-Tool kit (GTDB-Tk). Results: Our approach supported the recovery of ~1300 high-quality, phylogenetically diverse MAG across 8 bacterial phyla, including 35 "new" species, representing novel pathogenic and protective bacteria. The colonic MAM from healthy subjects possessed greater taxonomic diversity and a larger number of functional genes than the Crohn's disease subjects from both countries, but fewer of these genes could be assigned to reference taxa. As such, the colonic MAM from healthy subjects possesses novel forms of microbial "dark matter". There were 27 and 25 species unique to the Australian and Hong Kong Crohn's disease subjects, respectively, and another 14 species shared by both. Many of the functional gene classifiers differentiating Crohn's disease from healthy subjects were assigned to low prevalence taxa including Proteus, Acidaminococcus, and Fusobacterium. The dissimilarity scores of the colonic MAM were larger among the Crohn's disease subjects from both countries, suggesting more heterogeneity in Crohn's disease than in health. Conclusion: Here we use two populations with very different rates of Crohn's disease incidence to show the colonic MAM of healthy subjects in both countries are more diverse, less heterogenous, and contain a greater amount of functional and taxonomic "dark matter" than Crohn's disease subjects. Novel microbes have been identified and cultured, bringing genomes to life as microbial consortia and novel axenic isolates, to fully define their role in Crohn's disease pathogenesis or abrogation. 1 Teh JJ, Berendsen EM, et al., ISME J 2021;15:3326-3338. The ENIGMA study is supported by a grant from the Leona M. and Harry B. Helmsley Charitable Trust